Alcohol extract from Vernonia anthelmintica willd (L.) seed counteracts stress-induced murine hair follicle growth inhibition - Qian Wang; Yongxin Wang; Silin Pang; Jia Zhou; Jie Cai; Jing Shang (BMC, 2019)
Abstract Background Vernonia anthelmintica (L.) willd is a traditional urgur herb in China for a long history. Its alcohol extract (AVE) has been proved to promote hair follicle growth in C57BL/6 mice. We conducted this study to investigate the hair-growth effects of AVE in stressed mice and its possible mechanism of action. Methods The hair-follicle growth effects of AVE were examined by in vivo and in vitro study. We exposed C57BL/6 male mice to chronic restraint stress to induce murine hair follicle growth inhibition. The effects of AVE were examined by histological analysis, immunofluorescence for Ki67 and cytokeratin 19 immunoreactivity, western blot assay in tyrosinase and related proteins expressions and immunofluorescence for nerve fibers. In organ culture of mouse vibrissae follicles, we used substance P as a catagen-inducing factor of hair follicle growth, and measured the elongation of hair shafts and expression of neurokinin-1 receptor protein by application of AVE. Results Our results showed that AVE counteract murine hair follicle growth inhibition caused by chronic restraint stress via inducing the conversion of telogen to anagen and inhibiting catagen premature, increasing bulb keratinocytes and bulge stem cells proliferation, promoting melanogenesis, and reducing the numbers of substance P and calcitonin gene-related peptide nerve fibers. Furthermore, AVE also counteracted murine hair follicle growth inhibition caused by substance P in organ culture. Conclusion These results suggest that AVE counteract stress-induced hair follicle growth inhibition in C57BL/6 mice in vivo and in vitro, and may be an effective new candidate for treatment of stress-induced hair loss.